Non-intrusive Human Pose Sensing: A Comparative Review of Wi-Fi, Radar, and Inertial Sensing - Cui, Dongqi (Transactions on Computer Science and Intelligent Systems Research, 2025)
Non-intrusive human sensing has gained rapid momentum across smart homes, rehabilitation, safety monitoring and other applications. However, heterogeneous evaluation practices hinder fair cross-technology comparison. Thus, this paper focuses on three representative technologies—wearable sensors, radar sensing, and Wi-Fi sensing and consolidates reported findings onto a unified six-dimensional scheme: Accuracy, Response Speed, Cost, Privacy, Convenience, and Coverage. Those heterogeneous metrics are qualitatively mapped to high, medium, Low and visualized with radar charts. Based on these diagrams, this paper introduces a scenario requirement versus technology performance overlap procedure for scenario selection: the preferred option minimizes performance waste relative to the scenario’s needs while satisfying all critical-dimension requirements. An example of industrial robot collision detection demonstrates the workflow’s practicality and reusability. The paper also discusses limitations of the review methodology and future improvements, such as developing decision-making software. In conclusion, this paper provides a structured and actionable path for qualitative benchmarking and scenario-driven technology selection in non-intrusive human sensing.
Keywords: Non-intrusive human sensing; Wi-Fi sensing; Radar; Wearable sensors; Qualitative benchmarking.